A systematic review of effective bioagent in chronic wounds: The maggot biotherapy pyramid - Nevra Polat; Murat Koç; Hüseyin Ayhan; Salih Mollahaliloglu (Ankara Medical Journal, 2022)
Wound assessment is important in monitoring the effectiveness of treatment in chronic wounds. Therefore, a holistic approach is needed when evaluating effective wound treatment. Most chronic wounds require complementary treatment approaches and conventional treatments in modern medicine. This research was carried out by compiling studies on the past, present, and future of maggot (medical larvae) that cure nonhealing/hard-to-heal wounds; therapeutic larva types, therapy method, healing mechanism, wound healing effect with clinical studies, different usage areas and biological activities of the larvae and the metabolite components in the secretions that provide these activities. In conclusion, medical larvae applied with traditional and complementary medicine techniques to treat nonhealing, difficult-to-heal wounds have a wound-healing effect. However, more research is needed to identify the metabolite components in their secretions that provide their mechanism of action and biological activities.